Investigating the Moderating Effects of Self-Efficacy, Age and Gender in the Context of Nursing Mobile Decision Support Systems Adoption: A Developing Country Perspective - Jaradat, Mohammed-issa R; Imlawi, Jehad; Mashaqba, Abedalellah (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Health professionals are increasingly using and relying on mobile applications to support their decisions in Jordan. Nursing staff have the opportunity to use a wide variety of already existed mobile applications to support their tasks when providing health services to both inpatients and outpatients. This study attempted to investigate the key factors that affect adoption of mobile applications that support nursing staff health decision making in Jordan. These key factors include perceived usefulness, perceived ease of use, subjective norms, job relevance, perceptions of external control. In addition, this study intended to investigate the moderating effect of self-efficacy, age and gender. The study validated the proposed model using data collected from 241 nursing staff in three public and private hospitals in Jordan. Results show that perceived usefulness and perceived ease of use are the most important factors in determining individual’s behavioral intention to adopt the mobile application in their decision support processes.